Management of Educational Funds Through School Operational Assistance (BOS) in Elementary Schools in Sempaja Subdistrict - Lapaiku, Heriman; Hartini, Supri; Wartini, Sri; Warman, Warman; Mulawarman, Widyatmike Gede (Borneo Journal of Primary Education, 2024)
This study aims to describe and analyze the management and utilization of School Operational Assistance (BOS) funds in elementary schools in the North Sempaja sub-district. The BOS program is an educational policy designed to alleviate the financial burden on the community, especially after the rise in fuel prices. Adequate educational financing plays a crucial role in achieving the goal of quality education. This research uses a descriptive method with a qualitative approach, gathering data through interviews with school principals, vice principals, treasurers, and school committees, as well as documentary data related to BOS fund management. The results show that the management of BOS funds in elementary schools has been implemented according to the existing guidelines. However, there are still some challenges in the supervision and transparency of fund usage. BOS funds are used for various school operational needs, such as purchasing textbooks, teacher training, student activities, and facility maintenance. Despite contributions from the school committee or parents, supervision of BOS fund usage still needs improvement to ensure more transparency and accountability. Therefore, it is recommended to enhance the capacity of internal supervisors, deepen the understanding of the fund usage guidelines, and tighten supervision so that BOS funds can be used optimally and appropriately.